A pictorial key for the identification of beetle (Order: Coleoptera) and diversity study in selected area within Pelangai Forest Reserve, Negeri Sembilan, Malaysia - NURUL HUDDA ABDULLAH; IZZATI ADILAH AZMIR (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Abdullah NH, Azmir IA. 2021. A pictorial key for the identification of beetle (Order: Coleoptera) and diversity study in selected area within Pelangai Forest Reserve, Negeri Sembilan, Malaysia. Biodiversitas 22: 947-955. Beetles or Coleoptera were largely distributed in Asia, especially in Malaysia. The beetle was important in the ecosystem as a decomposer, pollinator, and bio-indicator of the habitat. However, the beetle could also be a potential pest to crops or plants that cause damage to many plantations. This study aimed to establish a key pictorial for beetle identification based on selected characteristics and to determine the beetle diversity, evenness, and genus similarity in Pelangai Preserved Forest, Negeri Sembilan at three different sites i.e., forest, open area, and the sub forested area. This study was carried out between February and March 2020. The Shannon Evenness Index (E) calculated species evenness and the Simpson’s Index (D) assessed the diversity of beetles in this research. The results obtained were 67 individuals of beetles comprised of 7 families and 13 genera. The most found beetle was genus Apogonia sp. (16.4%), followed by genus Epilachna sp. (14.9%), and genus Adoretus sp. A (14.9%) while the least found beetle was genus Blabephorus sp. (1.5%). Site C or sub forested area had the highest species similarity (E= 0.913), followed by Site B or open area (E= 0.912) and Site A or forest area with the lowest species similarity (E= 0.908). This showed that the species in the sub forested area were evenly distributed compared to the forest and open area. As for diversity index, sub forest had the highest diversity (D= 0.860), followed by open area (D= 0.845) and forest area with the lowest diversity (D= 0.188). In conclusion, the beetle from genus Rhyncophorus sp. was the most distinct among other beetles due to the presence of snout and visible head which make it easier to identify. Beetle from genus Apogonia sp. was most found in sub forested areas due to high vegetation and medium sun exposure. Sample collection can be increased in future study by using dung trap sample collection and longer sampling time.